2011
DOI: 10.1074/jbc.m111.267286
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of α2B-Adrenergic Receptor-mediated Extracellular Signal-regulated Kinase 1/2 (ERK1/2) Activation by ADP-ribosylation Factor 1

Abstract: Background: ERK1/2 activation by G protein-coupled receptors can be mediated through multiple pathways. Results: ␣ 2B -Adrenergic receptor interacts with ADP-ribosylation factor 1 (ARF1) to modulate ERK1/2 activation. Conclusion: ERK1/2 activation by ␣ 2B -adrenergic receptor is mediated through a novel pathway involving ARF1. Significance: The small GTPase ARF1 may function as an important regulator in receptor-mediated ERK1/2 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 51 publications
5
42
0
Order By: Relevance
“…During the studies of regulation of GPCR trafficking and signaling by ARFs [27, 28], we found that the activation the MAPK Raf1-MEKERK1/2 pathway by α 2B -adrenergic receptor (α 2B -AR), a typical GPCR, may be partially mediated through ARF1 [29]. In the current study, we have further defined the underlying molecular mechanism and the possible function of this ARF1-mediated MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…During the studies of regulation of GPCR trafficking and signaling by ARFs [27, 28], we found that the activation the MAPK Raf1-MEKERK1/2 pathway by α 2B -adrenergic receptor (α 2B -AR), a typical GPCR, may be partially mediated through ARF1 [29]. In the current study, we have further defined the underlying molecular mechanism and the possible function of this ARF1-mediated MAPK signaling pathway.…”
Section: Introductionmentioning
confidence: 75%
“…[ 3 H]-RX821002 (specific activity = 50 Ci/mmol) was from Perkin Elmer Life Sciences. All other materials were obtained as described elsewhere [29-31]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three ␣ 2 -ARs couple to the Gi/Go family G proteins, and their activation has been well shown to stimulate the mitogen-activated protein kinases (MAPK) ERK1/2, inhibit adenylyl cyclases, and suppress voltage-gated calcium channels (24,26,(37)(38)(39). To investigate if GGA3 knockdown-induced reduction of cell surface ␣ 2B -AR expression could result in a concomitant defective signaling, the activation of ERK1/2 and the reduction of cAMP production were chosen as functional readouts.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic AMP (cAMP) concentrations were measured by using the Cyclic AMP XP Assay kit (Cell Signaling Technology) as described previously (26). Briefly, HEK293 cells inducibly expressing ␣ 2B -AR were cultured in 6-well dishes and transfected with GGA3 siRNA or shRNA for 36 h and then incubated with tetracycline at 40 ng/ml for 24 h. The cells were then split into 96-well plates at a density of 1 ϫ 10 4 cells/well.…”
mentioning
confidence: 99%